Clinical Findings and Survival in Cats Naturally Infected with Feline Immunodeficiency Virus. (4th June 2013) - Liem, B.P.; Dhand, N.K.; Pepper, A.E; Barrs, V.R.; Beatty, J.A.
<x xml:space="preserve">Abstract</x> Background The clinical course and outcome of natural feline immunodeficiency virus (FIV) infection are variable and incompletely understood. Assigning clinical relevance to FIV infection in individual cats represents a considerable clinical challenge. Objective To compare signalment, hematologic and biochemical data, major clinical problem, and survival among client‐owned, FIV‐infected, and uninfected domestic cats. Animals Client‐owned, domestic cats tested for FIV (n = 520). Methods Retrospective, case control study. Logistic regression analyses were conducted to identify risk factors for FIV infection and to compare hematologic and biochemical data between cases and controls, after adjusting for potential confounders. Survival times were compared using Kaplan–Meier curves. Results The prevalence of FIV infection was 14.6%. Mixed breed, male sex, and older age were risk factors for FIV infection. Hematologic abnormalities, biochemical abnormalities or both were common in both FIV‐infected and uninfected cats. Lymphoid malignancies were slightly more common in FIV‐infected than uninfected cats. Survival of FIV‐infected cats was not significantly different from that of uninfected cats. Conclusions and Clinical Importance Multiple hematologic and biochemical abnormalities are common in old, sick cats regardless of their FIV status. Their presence should not be assumed to indicate clinical progression of FIV infection. A negative effect of FIV on survival was not apparent in this study.